ANALISIS FAKTOR KEGAGALAN PENGELOLAAN KOPERASI DI KABUPATEN PATI - Rahmadi Rahmadi (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
This study aims to (1) Describe the development of cooperatives in Pati, Central Java Province (2) Describe the impact of the failure of cooperative management in Pati Regency. (3) Ensuring that any Cooperative problems in Pati Regency can be faced and resolved so that the percentage of cooperatives that are dissolved is getting smaller. The method used in this research is a qualitative method of case study research. The technique used in data collection is done through participatory observation, interviews, and documentation by using data analysis that is carried out continuously from the beginning to the end of the study starting from collecting data, reducing data, presenting data and drawing conclusions. The results of this study indicate that: (1) Cooperatives in Pati Regency in 2017 were 1,143 cooperatives, 594 were active (51.97%), 549 were active (48.03%). (2) The consequences of the failure of cooperative management in Pati Regency, several cooperatives that were dissolved by the Cooperative Office and Regency UMKM, in 2018 a number of 527 cooperative units were dissolved. (3) Cooperative management in Pati Regency, some running well and smoothly, cooperatives that are active / well managed 29.38%, some others run poorly and not smoothly, cooperatives are not well managed / regular 21.68%